The uppermost monoterpenes improving Cinnamomum camphora thermotolerance by serving signaling functions - Xu, Chenyi; Wang, Bin; Luo, Qingyun; Ma, Yuandan; Zheng, Tiefeng; Wang, Yingying; Cai, Yuyan; Zuo, Zhaojiang (Frontiers in Plant Science, 2022)
Terpenes serve important functions in enhancing plant thermotolerance. Cinnamomum camphora mainly has eucalyptol (EuL), camphor (CmR), linalool (LnL) and borneol (BeL) chemotypes basing on the uppermost monoterpenes. To reveal the thermotolerance mechanisms of these uppermost monoterpenes (eucalyptol, camphor, linalool, and borneol) in C. camphora, we surveyed the ROS metabolism and photosynthesis in the 4 chemotypes fumigated with the corresponding uppermost monoterpene after fosmidomycin (Fos) inhibiting monoterpene synthesis under high temperature at 38oC (Fos+38oC+monoterpene), and investigated the related gene expression in EuL and CmR. Meanwhile, the thermotolerance differences among the 4 uppermost monoterpenes were analyzed. In contrast to normal temperature (28oC), ROS levels and antioxidant enzyme activities in the 4 chemotypes increased under 38oC, and further increased in the treatment with Fos inhibiting monoterpene synthesis at 38oC (Fos+38oC), which may be caused the alterations in expression of the genes related with non-enzymatic and enzymatic antioxidant formation according to the analyses in EuL and CmR. Compared with Fos+38oC treatment, Fos+38oC+monoterpene treatments lowered ROS levels and antioxidant enzyme activities for the increased non-enzymatic antioxidant gene expression and decreased enzymatic antioxidant gene expression, respectively. High temperature at 38oC reduced the chlorophyll and carotenoid content as well as photosynthetic abilities, which may result from the declined expression of the genes associated with photosynthetic pigment biosynthesis, light reaction, and carbon fixation. Fos+38oC treatment aggravated the reduction. In contrast to Fos+38oC treatment, Fos+38oC+monoterpene treatments increased photosynthetic pigment content and improved photosynthetic abilities by up-regulating related gene expression. Among the 4 uppermost monoterpenes, camphor showed strong abilities in lowering ROS and maintaining photosynthesis, while eucalyptol showed weak abilities. This was consistent with the recovery effects of the gene expression in the treatments with camphor and eucalyptol fumigation. Therefore, the uppermost monoterpenes can enhance C. camphora thermotolerance as signaling molecules, and may have differences in the signaling functions.